The metropolitan revolution : how cities and metros are fixing our broken politics and fragile economy - Katz, Bruce; Bradley, Jennifer (Brookings Institution Press, 2013)
Argues that the new American economy must be driven by exports and powered by cleaner energy and indicate that metropolitan areas should lead the way in this new economic landscape.